2010
DOI: 10.1007/s12094-010-0603-8
|View full text |Cite
|
Sign up to set email alerts
|

Professional survey on knowledge and clinical patterns of pain management in Spanish medical oncology

Abstract: Cancer pain is still not treated adequately. The barriers impeding its appropriate treatment include lack of knowledge, erroneous beliefs and inappropriate attitudes with regard to pain, which are sustained by some or all of those involved in the problem. The present study shows the results of an exploratory survey using a large sample of specialists in clinical oncology. Its main objective is to evaluate daily analgesic practices and compliance with clinical guidelines in order to identify areas that should b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 15 publications
0
5
0
1
Order By: Relevance
“…For further consideration are the results of a very recent Spanish survey31 reporting that a large percentage (between 2.9%–52%) of Spanish oncologists are unaware of certain concepts of potential clinical significance, such as the actions of drugs upon the different opioid receptors.…”
Section: Treatment Of Breakthrough Painmentioning
confidence: 99%
“…For further consideration are the results of a very recent Spanish survey31 reporting that a large percentage (between 2.9%–52%) of Spanish oncologists are unaware of certain concepts of potential clinical significance, such as the actions of drugs upon the different opioid receptors.…”
Section: Treatment Of Breakthrough Painmentioning
confidence: 99%
“…The SEOM (Spanish Society for Medical Oncology) recommendations29 and ESMO30 and EAPC guidelines8 state that ROOs should be considered first-line treatment for BTcP. In 2008, a survey conducted in Spain reported that fentanyl was largely the opioid most commonly used for treating cancer pain 31. Indeed, clinicians showed appropriate knowledge in the safe and effective use of rapid-onset fentanyl preparations.…”
Section: Discussionmentioning
confidence: 99%
“…Son escasos los estudios en los que haya abordado de manera rigurosa la comparación entre las distintas opciones para establecer cuál o cuáles son las que presentan un mejor balance riesgo-beneficio (9). No obstante, una encuesta de ámbito español publicada en 2010 mostró que un alto porcentaje de los oncólogos desconoce algunos conceptos de potencial importancia clínica, como las acciones de los medicamentos sobre los diferentes receptores de opiáceos (37). Aunque el consenso es claro con respecto a la administración de fentanilo de absorción rápida para el tratamiento del DIO y los oncólogos españoles ven el fentanilo transmucoso como una terapia eficaz, parece prioritario un esfuerzo para divulgar los aspectos técnicos que permitan al oncólogo conocer a fondo las distintas opciones terapéuticas.…”
Section: Discussionunclassified